Pengaruh Kombinasi Sitokinin dan Gibberelin terhadap Pemanjangan Tunas Jambu Mete (Anacardium Occidentale L.) secara In Vitro - Ariyanti, Febrina; Tumilisar, Christiani; Yunita, Rossa (LPPM Universitas Negeri Jakarta, 2014)
Abstract Cashew (Anacardium occidentale L.) is a plant with high economic value. Conventional propagation of this plant still has obstacles, so an alternative techniques using tissue culture could be tried. One of the factors that determine the success of tissue culture techniques is the type and concentration of growth regulators was used. Growth regulator which have effect on shoot elongation is a cytokinin and gibberellin, this research tried to investigate the influence of combination cytokinin and gibberelin on in vitro shoot elongation of cashew. This research was conducted at BB-Biogen, Bogor on June-November 2010. The method in this research was to design experimental method with completely randomized design. The result was cytokinin could increase the length of shoots and quantity of shoots very well until 4 cm and quantity of shoot for 5. With the most effective cytokinin is zeatin of 5 mg/l. Key words: Anacardium occidentale L., cytokinin, elongation of shoots, gibberelin